The Combined Effect of Market Orientation and Owner/Manager's Innovativeness on Innovation and Business Performance of Small and Medium Sized Manufacturing Firms in Pakistan - Alam, Muhammad Masroor (2009)
The study investigated various aspects of market orientation and owner/manager's innovativeness relationship with innovation and performance in the small and medium sized manufacturing firms in Pakistan. The objectives of the study were 1) to examine the relationship and effect of market orientation and owner/managers innovativeness in relation to innovation and performance, 2) to examine the relationship and effect of innovation in relation to performance, 3) to examine the combined effect of owner/managers innovativeness and market orientation in relation to innovation and performance, and 4) to examine the level of owner/manager's innovativeness and market orientation based on firm's and respondent's characteristics. This study used owner/manager's innovativeness, market orientation and innovation as they relate to firm overall performance. The innovativeness constructs used to measure the owner/manager's innovativeness and domain specific innovativeness had been widely used in consumer research studies. Based on the theories of Ricardian (1871), Penrose (1959), Schumpeter (1934) and Roger's Adoption of Innovation concept (2003), a model of relationship was proposed and developed to examine the relationships between market orientation, owner/manager's innovativeness, innovation and the small and medium sized firms' performance. To test the relationship of the variables in the model, data from 170 textile and apparel/garment manufacturing small and medium sized firms in Karachi-Pakistan were used. To test the relationship hypotheses of the study, correlation, multiple regression analysis, T-test and ANOVA were performed. The correlation analysis suggested a significant and positive relationship among all the four variables used in the model. Multiple regression analysis result indicated that owner/manager's general innovativeness as well as innovativeness in product-strategy and process domain has a significant influence on the overall innovation. The general innovativeness and innovativeness in product-strategy domain also significantly influenced the firm performance. Results from correlation and multiple regression analysis further suggested that market orientation and its three components appeared to be associated directly with innovations and firm performance. However customer orientation, which is one of the key variables, appeared to cause a main effect on firm overall innovation and also SMEs overall performance. It is also proven in this study that among the three innovation strategies, only product innovation significantly influenced the firm performance. One-way ANOVA results indicated that a significant difference of the level of owner/manger's general innovativeness and domain specific innovativeness in product-strategy and process domain. The result confirmed that younger managers and owners with higher qualification had better scores on innovativeness scale than the older and less qualified owner/managers. Other results of One-way ANOVA indicated that export oriented manufacturers were more market oriented than the non-export oriented. The results findings further confirmed that small and medium-sized firms can be market oriented at any stage of their life cycle and did not need to be established firms in the industry for being market oriented. Findings of this study showed that owner/manager's innovativeness permeated all the variables in the model and had a positive influence to market orientation, innovation and firm performance. The study confirmed the existence of the linear relationship between all the variables and in relation to SMEs performance, and further suggested that manufacturing textile SMEs must focus on innovative owners and managers, who could build a strong market orientation culture for the firm and greater level of adoptions of innovations and firm performance.